Assessing Design of Drip Emitters by Evaluating Hydraulic and Manufacturing Performance of Online Drip Emitters - , Kunapara A. N., Subbaiah R., Patel G. R. (Archives of Current Research International, 2024)
The efficiency of drip irrigation is closely influenced by the accuracy of its design, particularly the hydraulic and manufacturing performance of the emitters. This study investigates the hydraulic performance and flow variation of 8 litres per hour (lph) drip emitters. Discharge rates for 100 emitters were measured at a pressure of 1 kg/cm² to determine the manufacturer's coefficient of variation and the flow variation due to hydraulic factors. The relationship between pressure and discharge was modelled using power function regression, demonstrating a strong correlation between predicted and observed emitter discharge rates, with a root mean square error (RMSE) of 0.56 lph. A design chart was derived from this model, illustrating the relationship between input pressure at the head end and output pressure at the tail end of the system. The manufacturing coefficient of variation for the 100 emitters was found to be 0.0521, classifying the emitters as "good" according to manufacturing standards. The study provides important understandings for designers aiming to create efficient drip irrigation systems and effective water management strategies. By addressing both hydraulic and manufacturing variations, the study confirms that it is possible to achieve more uniform water distribution, enhance crop yield, and optimize resource utilization.